Feel these words : writing in the lives of urban youth - Weinstein, Susan (Albany, New York : State University of New York Press, 2009)
"A work that captures the elusive nature of writing for today's youth, this narrative lets us in on how young people see writing in their multiple worlds. Keenly aware of ways to create a spectrum of types and purposes of writing, the young composers, entrepreneurs, and community members portrayed here will give writing teachers, journalism leaders, and the entertainment industry a new perspective." -- Back cover
Acknowledgments -- Introduction -- "I am me but who am I?": presenting the writers -- "You never let me speak": power, language, and learning -- "Questioning myself and the people around me": identifications and communality in imaginative writing -- "You gotta be a writer to get in the game": understanding rap as a literate discourse -- Pregnancy, pimps & "clichéd love things": writing through gender and sexuality -- "My work sparked an interest in someone else": the pleasures of imaginative writing -- "I'm book smart, street smart & everything in between": writing, literate identity, and academic achievement -- "If you can't write you can't succeed": changing attitudes among educators and youth -- Epilogue: where are they now? -- Appendix -- Notes -- Works cited -- Index.
Includes bibliographical references and index.
Keywords: CREATIVE WRITING (SECONDARY EDUCATION -- ILLINOIS -- CHICAGO -- CASE STUDIES); ENGLISH LANGUAGE -- COMPOSITION AND EXERCISES --STUDY AND TEACHING -- CASE STUDIES